Analysis of Factors Affecting Quality of Life in Type II Diabetes Mellitus Patients at Anshari Saleh Hospital Banjarmasin - Sarri, Aulya Aprina; Ilmi, Bahrul; Solikin, Solikin; Syafwani, M; Ruslinawati, Ruslinawati (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Type II diabetes mellitus is characterized by high blood sugar levels that trigger complications and reduce the quality of life physically, psychologically, socially, and environmentally. Quality of life is used to evaluate the effectiveness of interventions and monitor public health. The purpose of the study was to analyze the most influential factors on the quality of life in patients with type II diabetes mellitus at Anshari Saleh Hospital, Banjarmasin. The research method used Cross-sectional with Purposive Sampling technique of 83 respondents. The independent variables were age, gender, education, income, complications, duration of suffering, family support and the dependent variable of quality of life using bivariate with Chi-Square, while multivariate analysis with multiple logistic regression used the WHOQOL-BREF questionnaire as an instrument of quality of life. The results of the study showed that there was an influence between education level (p = 0.000), income level (p = 0.008), disease complications (p = 0.002), duration of suffering (p = 0.021), family support (p = 0.021) and education level factors (OR = 60,527) which had the most influence on the quality of life in patients with type II diabetes mellitus. Education level affects the quality of life of diabetes sufferers through understanding and managing the disease. Higher education makes it easier to understand health information, improving quality of life. Meanwhile, low education can reduce quality of life due to difficulty understanding information even though broad knowledge can improve the situation. However, lack of awareness to behave healthily still has a negative impact on the quality of life physically, psychologically, socially, and environmentally. It is hoped that nursing services will provide more continuous education by forming peer groups (diabetes classes), and WhatsApp groups to improve health education for type II diabetes mellitus sufferers according to their level of education in increasing their knowledge.